Analisis Karakter Bahasa Alay Kaum Remaja Di Kota Makassar - Matius Tinna Sarira (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2019)
In daily life, human being can never escape from language. There are two types of languages; the standard language and the non-standard languages. In Indonesia, the standard language is Bahasa Indonesia, while the non-standard languages are the languages of vernacular (local languages) and sub-cultural languages (slang, jargon, etc). Nowadays, most of teenagers use the nonstandard language to communicate among their friends, which is called slang. There is a newslang in Indonesia which is called Alay language. The Alay language is popular among teenagers since 2008 until now. The purpose of this study were (1) to know the patterns used to modify Alay Language, (2) to know the effect of using Alay language on the standard form of Indonesian language, and (3) to find out the purpose of Alay Language used by teenagers in Makassar. This research uses descriptive analysis method. The research data were taken from the conversations that contained of Alay's words, which were previously made on the internet by Facebook social network users. Other supporting data were the questionnaires. The results of this study indicated that (1) There were no standard rules in modifying Alay Language, but the most common process was Substitution Process with a frequency of 38%. (2) The use of Alay Language had both the positive and negative effects on the existence of standard language, Indonesian language. (3) One of the reasons of using the Alay language was to be called “cool”.